NBP, baza monetarna i stagnacja polskiej gospodarki - Więznowski, Artur (National Bank of Poland, Monetary Base and Stagnation of Polish Economy, 2005)
A thesis that intentional decreasing of monetary base by NBP was one of important factors responsible for slowing down of Polish economy in the years 2001-2002 is formulated and verified in the article. To keep the money supply dynamics and inflation inside a stated target, NBP decided to shrink the monetary base. Unfortunately, a big part of Polish economy uses bank money only in limited amounts and dominated by cash as medium of exchange. It is why NBP policy touched countryside, small towns and small and medium enterprises most. The author tries to prove that not only aggregates money supply is important for the economy, but also its structure. The analysis of data for chosen developed economies indicated as well, that the absolute decrease in monetary base was a rare event and was accompanied by unpleasant consequences in the form of increase in unemployment and slow down of the growth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 21-27